The interaction of salinity, drought and temperature on seed germination and seedling characteristics of lemon balm (Melissa officinalis L.) - E. Nozarpour; R. Tavakkol Afshari; N. Majnoun Hosseini (علوم و فناوری بذر ایران)
This study was conducted to evaluate the effects of water potential and temperature on seed germination rate of lemon balm (Mellissa officinalis L.). Temperatures used in this experiment had 10 temperature levels including 5, 10, 15, 20, 23, 25, 27, 30, 32 and 35 ° C. At each temperature the effect of salinity levels (0, -0.2, -0.4, -0.6 and -0.8 MPa of Sodium chloride) and the effect of drough levels (0, -0.2, -0.4, -0.6 and -0.8 MPa of Polyethylene glycol) on germination characteristics was studied. This study was conducted in Seed Laboratory, College of Agriculture and Natural Resources, University of Tehran in Karaj in 2015. Data were analyzed using factorial design in a completely randomized design with four replications. The results showed that the effect of temperature and water potential was significant on germination indices. Traits studied were germination percentage, germination rate, root and shoot length and seedling vigor index. The germination percentage and germination rate of lemon balm decreased linearly by increasing salinity and drought stress. In both experiments, the highest (90%) and lowest (20%) germination percentage was observed in control and the potential of -0.8 MPa, respectively. Seedling vigor index decreased by decreasing water potential and increasing in salinity level. Lemon balm seeds did not germinated in 5, 10, 15 and 35 ° C in any moisture levels. The results can be used for future studies on the seed ecology of lemon balm.